Expressão gênica no desenvolvimento adulto de operárias de Frieseomelitta varia - Jaskot, Michael Christopher (2018)
Global declines in pollinators have served as the impetus for the widespread study of hymenopterans. The molecular processes controlling detoxification and antioxidant pathways are of supreme importance to insects that are in contact with the possible causes of these declines, such as pesticides, xenobiotics and pathogens. As hymenopterans such as Apis mellifera have been thoroughly studied with regards to their genetics and hormone titers, we desired to uncover if similar molecular characteristics are found in less-frequently managed eusocial bees. The phenomenon of temporal polyethism, present in numerous bee species, can also be investigated with regard to the modulation of genetic expression across age and task groups. However, the levels of genetic expression among detoxification, xenobiotic degradation, antioxidant, defense, developmental and ageing pathways in the Brazilian stingless bee Frieseomelitta varia are not studied and specific information pertaining to these processes are generally unknown to science. In this study, variations in the genetic expression of genes from different families and functional categories (related to the progression of adult development (longevity/ageing) and/or involved in the general mechanisms of defense (detoxification/xenobiotics, antioxidants and the immune system)) were investigated in workers of the bee Frieseomelitta varia by means of semiquantitative RT-PCR (Reverse Transcriptase Chain Reaction) in three age groups: new workers (~ 0-5 days), intermediates (~ 12-19 days) and foragers (~ 29-50 days). P450 6aq1 showed uniform expression in the three groups, while two genes from the same family, shade and spook, were up regulated in new bees. The antioxidants sod and cat were expressed with the same pattern of up regulation in new and intermediate bees. Relish and dorsal, transcription factors in defense pathways, were up regulated in new bees. High levels of gst-s1 and gst-s4 transcripts were found, signifying that in the three groups detoxification pathways are active. Transcriptome data was also analyzed (RNA-seq, Illumuna) using the integument of recently-emerged workers and foragers. RT-PCR and RNA-seq data demonstrate that the molecular behavior of some genes found in other species, such as A. mellifera, is similar to what is observed in F. varia. Coinciding with scientific literature, the gene coding for juvenile hormone esterase (jhe) is expressed in similar levels in new and intermediate bees, and both significantly more expressed than in foragers. The gene coding for vitellogenin (vg) showed to be greatly expressed in the intermediate phase, compared to the lower levels found in new and foraging bees. Such data suggest that the double repressor hypothesis of juvenile hormone and vg, described in A. mellifera, is also valid for F. varia adults RNA-seq data was also compiled and analyzed for P450, GST and CCE families as well as other detoxification and metabolic pathway constituents. P450 genes were generally found to be up regulated in foragers, suggesting more of a detoxification role rather than developmental. Two of the three GST genes surveyed were found to be highly up regulated in newly emerged adults. Expression of antioxidant genes varied greatly, suggesting specific roles for each protein at a certain developmental stage. Expression of developmental genes also varied, yet several of the gene surveyed, chico, foxo, calponin and kruppel were concomitantly expressed do to their interdependence in molecular circuitry. Genes such as hexamarin-110 and hexamarin-70b were found to be extremely up regulated in newly emerged adults, agreeing with their known role in amino acid storage to facilitate growth during adult stages. Of great interest was the almost universal up regulation of immune response and defense genes in foragers, bolstering the assertion that these individuals will need higher levels of antimicrobial peptides (AMPs) to defend themselves from pathogens located outside of the hive. The use of F. varia in research has shown the importance of understanding the genetic processes in all hymenopterans, while adding information to the data of already well-known species, such as A. mellifera.